TRAINING OF SCIENTIFIC PAPERS WRITING FOR HIGH SCHOOL TEACHER TO IMPROVE THE QUALITY OF THE TEACHER - Rina Herowati; Gunawan Pamuji Widodo; Supriyadi Supriyadi; Sunarti Sunarti; Yane Dila Keswara; Nuraini Dewi Purnamasari (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2018)
ABSTRACTThe professional development of the teachers through the writing of scientific papers needs to be improved. The obstacle faced by teachers so they did not write scientific paper mainly are caused by limitation of time and not understanding the rules of writing a scientific paper. This devotional activity aims to improve  teachers' motivation to write scientific papers and improve the ability for the teachers to write scientific papers to produce as many articles as published in scientific journals. The method used is situational analysis by interviewing the principal and distributing questionnaires. Furthermore, the preparation of materials, lectures and discussions, as well as accompaniment of scientific writing until the participants successfully publish their articles in scientific journalsKeywords: quality improvement, scientific papers, teachers ABSTRAKPengembangan profesionalitas guru melalui penulisan karya ilmiah perlu ditingkatkan. Kendala yang dihadapi guru sehingga tidak menulis karya ilmiah terutama adalah belum ada waktu dan belum paham aturan penulisan karya ilmiah. Kegiatan pengabdian ini bertujuan untuk meningkatkan motivasi guru menulis karya ilmiah dan  meningkatkan kemampuan guru menulis karya ilmiah hingga dihasilkan sebanyak mungkin artikel yang dipublikasikan di jurnal ilmiah. Metode yang dilakukan adalah analisis situasi dengan wawancara dengan kepala sekolah dan penyebaran kuesioner.  Selanjutnya dilakukan penyusunan materi, ceramah dan diskusi, serta pendampingan penulisan karya ilmiah hingga peserta berhasil menerbitkan artikelnya di jurnal ilmiah.KataKunci: guru, karya ilmiah, peningkatan kualitas